Application of Realistic Mathematics Education (RME) Strategy in Learning Mathematics in MI/SD - Salsabila Saragih (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
This study aims to describe Realistic Mathematics Education (RME) learning strategies and to see the effect of these strategies on learning mathematics in MI/SD. This study uses a qualitative method, which is a research method that provides more analytical and subjective explanations. In this method the researcher uses the perspective of the participants as a preferred description in obtaining research results. From the results of the study it can be concluded that the RME strategy is very influential on students because with this strategy students are more interested in learning mathematics. Because this strategy is implemented by placing the reality and experience of students as the starting point in the learning process.